In situ radiochemical doping of functionalized inorganic nanoplatforms for theranostic applications: a paradigm shift in nanooncology - Sanchita Ghosh; Yutong Liang; Weibo Cai; Rubel Chakravarty (Journal of Nanobiotechnology)
Abstract In situ radiochemical doping presents a transformative approach for synthesizing radiolabeled inorganic nanoparticles (NPs) for cancer theranostics. Traditional radiolabeling techniques rely on bifunctional chelators, which often require harsh reaction conditions that can degrade the physicochemical properties of NPs. Additionally, the enzymatic dissociation of radiometals can potentially induce in vivo toxicity. In contrast, in situ doping directly incorporates radiometals into the NP crystal lattice, significantly enhancing both radiolabeling yield and radiochemical stability. This method preserves the pharmacokinetic profiles of the radiolabeled NPs, improving their theranostic efficacy. This review provides an up-to-date overview of the progress made in the development of radiolabeled inorganic nanoplatforms through in situ doping, with a focus on their stability, physicochemical characteristics, and applications in cancer theranostics. Our findings highlight the advantages in situ doping as a more efficient and stable alternative to conventional radiolabeling methods, offering substantial potential for the development of more effective cancer theranostic agents. Graphical Abstract